Bioengineering stents with proactive biocompatibility. (December 2015) - Yu, Young; Wise, Steven G; Celermajer, David S; Bilek, Marcela M M; Ng, Martin K C
Percutaneous coronary intervention has revolutionized the treatment of coronary artery disease. Successive improvements in implantation techniques, stent materials and design, combined with dual antiplatelet therapy have improved stent safety. However, optimal biocompatibility and long-term effectiveness in the absence of pharmaceutical intervention remains elusive. Drug-eluting stents, introduced to combat in stent restenosis was found to impair endothelial regeneration, increasing thrombotic risk. Innovations in polymer technology and new stent designs have improved but not solved these issues. Despite the drawbacks of drug elution it remains a key component of stent platforms, leaving the need for a truly biocompatible platform with lasting clinical efficacy and safety unmet. This review will examine current stent designs and explore proactive approaches to enhance stent biocompatibility.